2017
DOI: 10.5812/jogcr.10991
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Association of Lower Uterine Segment Involvement with Deep Myometrial Invasion in Endometrial Adenocarcinoma

Abstract: Background: Endometrial carcinoma is the most common cancer of the female genitalia and its prevalence is 2% to 3% along the females' lifetime. This adenocarcinoma is diagnosed in the early stages because the patients become symptomatic early in the course of disease. The correlation of the lower uterine segment involvement (LUSI) with the recurrence, and the survival rates in patients with endometrial adenocarcinoma are always questionable. Confirming the prognostic significance of LUSI can fundamentally impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…The current study showed that the mean age in females in whom LUS was involved in corpus located endometrioid adenocarcinoma is 55.39 ± 11.17 years versus 58.33 ± 10.33 years in females without such involvement with no significant statistical difference, it also showed that there is a non-significant statistical association with FIGO grade, this results disagree with one Turkish study done by Erkaya et al [17] and one Iranian study done by Aminimoghaddam et al [19] in which LUS involvement by endometrial carcinoma, in general, was used as a study group thus clarifying the disagreement with the current study. However, this is the only published studies worldwide searching for this purpose.…”
Section: Table 4: the Association Between Lower Uterine Segment Invol...contrasting
confidence: 97%
See 1 more Smart Citation
“…The current study showed that the mean age in females in whom LUS was involved in corpus located endometrioid adenocarcinoma is 55.39 ± 11.17 years versus 58.33 ± 10.33 years in females without such involvement with no significant statistical difference, it also showed that there is a non-significant statistical association with FIGO grade, this results disagree with one Turkish study done by Erkaya et al [17] and one Iranian study done by Aminimoghaddam et al [19] in which LUS involvement by endometrial carcinoma, in general, was used as a study group thus clarifying the disagreement with the current study. However, this is the only published studies worldwide searching for this purpose.…”
Section: Table 4: the Association Between Lower Uterine Segment Invol...contrasting
confidence: 97%
“…The present study found that there is a significant association between LUS involvement by endometrioid ca and FIGO stage, these results agree with a similar study done by Ogden et al [20], while Erkaya et al [17] and Aminimoghaddam et al [19] found a significant relationship between LUS involvement by endometrial ca in general and deep myometrial invasion which is an important criteria that define stage I endometrial cancer.…”
Section: Table 4: the Association Between Lower Uterine Segment Invol...supporting
confidence: 93%